Conversations on Covid-19: a viewpoint on care, connections and culture during the pandemic from a teacher educator and an Irish Traveller. Issue 2 (3rd April 2021) - Colum, Miriam; Collins, Annmarie
Abstract : In March 2020 when life as we know it changed, we adhered to a new set of rules and a new normal that Covid-19 imposed on not only the population of Ireland but on the entire world. Throughout this experience, the co-authors of this paper engaged in a series of phone, email, Zoom and WhatsApp conversations, reflecting on how their lives changed and what that meant for them as a teacher educator/project coordinator and student on the Tobar programme in Marino Institute of Education. Tobar is a Higher Education Authority funded initiative aimed at increasing participation in initial teacher education for members of the Travelling community. Drawing on a narrative inquiry approach, the co-authors present vignettes of their respective situations on Tobar during the pandemic. Care, connections, and culture were strong themes that emanated from the conversations. Notwithstanding strict limitations, the relational dimension of Tobar was further cultivated and maintained in these unprecedented times.